Hjertemenneske: Samtale med professor i kardiologi Jens Flensted Lassen - Kølle Martinsen, Lone (Slagmark - Tidsskrift for idéhistorie, 2020)
A Conversation with Cardiologist and Professor Dr. Jens Flensted Lassen. The essay is a conversation with cardiologist Jens Flensted Lassen about the cultural history of the heart, the connections between the humanities and the hard sciences.